Ander & Santi were here : a novel - Garza Villa, Jonny (Wednesday Books, 2023)
Nonbinary teen Ander is ready to leave their family's taquería and focus on their art, but when Santi, an undocumented immigrant from Mexico, begins to work at the restaurant, the two teens spark a romance made complicated by immigration police.